2020
DOI: 10.3389/fchem.2020.00744
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Structural-Function Relationship of Manganese(III)-Iodosylarene Adducts

Abstract: Metal-iodosylarene complexes have been recently viewed as a second oxidant alongside of the well-known high-valent metal-oxo species. Extensive efforts have been exerted to unveil the structure-function relationship of various metal-iodosylarene complexes. In the present manuscript, density functional theoretical calculations were employed to investigate such relationship of a specific manganese-iodosylbenzene complex [Mn III (TBDAP)(PhIO)(OH)] 2+ (1). Our results fit the experimental observations and revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…As shown in Figure 1, pathway A via 5 TS1 is the most feasible route to the oxidation product in the reaction between CHD and 1 , which has an energy barrier of 20.7 kcal/mol. This barrier is 5.8 kcal/mol higher than that for DHA, which is consistent with the fact that CHD has a stronger C─H bond than DHA 7 …”
Section: Methodssupporting
confidence: 81%
See 4 more Smart Citations
“…As shown in Figure 1, pathway A via 5 TS1 is the most feasible route to the oxidation product in the reaction between CHD and 1 , which has an energy barrier of 20.7 kcal/mol. This barrier is 5.8 kcal/mol higher than that for DHA, which is consistent with the fact that CHD has a stronger C─H bond than DHA 7 …”
Section: Methodssupporting
confidence: 81%
“…Further, Wang and co‐workers studied the mechanism of the C─H bond activation of dihydroanthracene (DHA) by 1 through density functional theory (DFT) calculations. Their DFT results suggested that there is a rate‐determining hydride transfer in the first step of the reaction 7 . However, there still remain uncertainties regarding the nature of the hydride transfer and other mechanistic possibilities.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations